Narrative review investigating the nephroprotective mechanisms of sodium glucose cotransporter type 2 inhibitors in diabetic and nondiabetic patients with chronic kidney disease - Speedtsberg, Emma S.; Tepel, Martin (Frontiers in Endocrinology, 2023)
Background and Aims: Outcome trials using sodium glucose cotransporter type 2 inhibitors have consistently shown their potential to preserve kidney function in diabetic and nondiabetic patients. Several mechanisms have been introduced which may explain the nephroprotective effect of sodium glucose cotransporter type 2 inhibitors beyond lowering blood glucose. This current narrative review has the objective to describe main underlying mechanisms causing a nephroprotective effect and to show similarities as well as differences between proposed mechanisms which can be observed in patients with diabetic and nondiabetic chronic kidney disease. Methods: We performed a narrative review of the literature on Pubmed and Embase. The research string comprised various combinations of items including “chronic kidney disease”, “sodium glucose cotransporter 2 inhibitor” and “mechanisms”. We searched for original research and review articles published until march, 2022. The databases were searched independently and the agreements by two authors were jointly obtained. Results: Sodium glucose cotransporter type 2 inhibitors show systemic, hemodynamic, and metabolic effects. Systemic effects include reduction of blood pressure without compensatory activation of the sympathetic nervous system. Hemodynamic effects include restoration of tubuloglomerular feedback which may improve pathologic hyperfiltration observed in most cases with chronic kidney disease. Current literature indicates that SGLT2i may not improve cortical oxygenation and may reduce medullar oxygenation. Conclusions: Sodium glucose cotransporter type 2 inhibitors cause nephroprotective effects by several mechanisms. However, several mediators which are involved in the underlying pathophysiology may be different between diabetic and nondiabetic patients.